PENGEMBANGAN VIDEO PEMBELAJARAN MENGGUNAKAN APLIKASI RENDERFOREST PADA MATERI PENTINGNYA AIR BAGI TUBUH MANUSIA - Mila Anisah; Yuyun Elizabeth Patras; Nurlinda Safitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Mila Anisah. 037120031. This research aims to develop and determine the feasibility of learning videos using the Renderforest application on the importance of water for the human body in class IV at SD Negeri Parung Tanjung 02, Bogor Regency. This research method uses the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. This research involves one lecturer each, a media expert and a language expert. The subjects in this research were class IV students at SD Negeri Parung Tanjung 02 Bogor Regency for the 2023/2024 academic year with a total of 21 students. From the research results it can be concluded that learning videos using the Renderforest application are very suitable for use in learning. This is based on the results of the validation carried out by the validator. The final validation results were obtained by media experts at 92%, language experts at 100%, material experts at 96% which are included in the